A systematic review of pedestrian injuries on account of distraction by mobile phone use. (7th October 2012) - Sotiraki, M; Matsoukis, I; Kousoulis, A; Gerakopoulou, P; Bouka, E; Alexopoulos, A; Petridou, E
Abstract : Background: Pedestrians, the largest group of road users, sustain a considerable proportion of road casualties, mainly due to their vulnerability. The association of accidents with driver's distraction by mobile phone (MP) use has been repeatedly documented, whereas the relation with pedestrian's MP use distraction has been less intensively studied. Purpose: To systematically review publications on accidents/ near-accidents due to pedestrian distraction by MP and attempt to quantify the risk. Methods: Ιn the context of the 'ENIGMA' program, aiming to summarise evidence on human risks associated with MP use, we systematically searched Medline publications using appropriate search algorithms and analysed eligible studies, published until February 2012. Results: Studies conducted in either virtual or real environments seem to point to an increased accident/near-accident risk due to pedestrians' distraction of attention by MP. Regardless of individual attentional/processing skills or the content of conversation, pedestrians who used MP while walking missed more opportunities for safe road behavior, needed more time to cross the street, left less safe time between their crossing and the next-arriving vehicle and were hit or almost hit more times compared to not distracted, Of note, pedestrians were less attentive to traffic, even when they may have made the appropriate motions to look left and right before crossing. Significance: MP use by pedestrians seems to impart a higher risk of being involved in an accident/near accident. Intensive efforts are needed aiming to highlight dangers and promote behaviour modification towards intended use of a new technology that has rapidly become highly popular.